SISTEM PEMASARAN GAMBIR DI SUMATERA BARAT (Kasus di Kecamatan Kapur IX, Kabupaten Lima Puluh Kota) - Amelira Haris Nasution; Ratna Winandi Asmarantaka; Luqman M Baga (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Gambier  is  one  of  the  commodity  export  in  Indonesia  and  it  has  been supplied  80%  of  the  world’s  needs.  The  largest  gambier  production  area  is  Lima Puluh  Kota  Regency,  West  Sumatera  (70,39%).  The  benefit  from  its  position  as  the biggest  gambier  supplier  or  producer  is  not  enjoyed  by  gambier  farmer  because  of weak gambier marketing  and  the role of  merchand middlement had a more powerful and dominant  for  determine  of gambier prices.  The purpose of this study  is  analyzing marketing  system  of  gambier  through  marketing  channel  analysis,  marketing channel’s  role  analysis  (farmer  group  and  merchand  middlemen)  and  operational efficiency analysis. This study was conducted from Desember 2014 until January 2015 in  Kapur  IX  Subdistrict,  Lima  Puluh  Kota  Regency,  West  Sumatera.  Farmer s  were chosen  by  purposive  sampling  method  and  middlemen  were  chosen  by  snowball sampling  method. Data processing  in this study was  using  descriptive qualitative and quantitative  analysis.  The  result  of  this  study  showed  that  there  are  4  marketing channels  of  gambier  marketing.  Based  on  operational  efficiency  indicator,  all marketing channels had been inefficiency because of weak farmer’s bargaining power so their  role is just as a price taker. But  among all  marketing channels, channel  4  is more  efficient  relatively  based  on  benefit and cost  ratio,  price  share  and  marketing function implementation. The result of this  study  also  showed that farmer  group  and farmer  association  of  gambier  are  still  in  starter  institution  so  that  they  are  not capable to contribute in marketing gambier.